2020
DOI: 10.1002/mds.28202
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolites Are Associated With Symptoms and Nigral Pathology in Parkinson's Disease

Abstract: A BS TRACT: Background: The objective of this study was to determine whether neurotoxic kynurenine metabolites, induced by inflammation, in plasma and cerebrospinal fluid (CSF) are associated with symptom severity and nigral pathology in Parkinson's disease (PD). Methods: Clinical and MRI data were obtained from 97 PD and 89 controls. We used ultra-performance liquid chromatography to quantify kynurenine metabolites and high-sensitivity multiplex assays to quantify inflammation in plasma and CSF. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 36 publications
6
60
0
Order By: Relevance
“…We report significant increases in Burkholderiales which is a bacterial genus with a broad environmental distribution [ 41 ]. Burkholderia can cause severe inflammation in immunocompromised individuals [ 41 ] and produce kynurenine and quinolinate [ 42 ], which are proinflammatory metabolites associated with symptom severity in PD [ 43 ]. Burkholderia has also been reported to infect the brain [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We report significant increases in Burkholderiales which is a bacterial genus with a broad environmental distribution [ 41 ]. Burkholderia can cause severe inflammation in immunocompromised individuals [ 41 ] and produce kynurenine and quinolinate [ 42 ], which are proinflammatory metabolites associated with symptom severity in PD [ 43 ]. Burkholderia has also been reported to infect the brain [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated elevated interleukin (IL)-6 levels in COVID-19, and one report suggested that the kynurenine pathway is perturbed [ 8 ]. Interestingly, these are both mechanisms that have been associated with PD [ 2 , 9 ].…”
mentioning
confidence: 99%
“…Recent work has also revealed that tryptophan metabolism is deranged in PD and represents a potential therapeutic target. PD patients have markedly elevated 3-HK in plasma and reduced 3-HANA [ 110 ]. KA is significantly reduced and QA levels correlated with disease severity in these patients, indicating a potential pathogenic role of TPH metabolites in exacerbating excitotoxic injury, though a causal role remains to be established.…”
Section: Tryptophan Metabolites In Neurodevelopment Neurologic Anmentioning
confidence: 99%